PENGENALAN PAKET DASAR BUDIDAYA HIDROPONIK UNTUK JENJANG PENDIDIKAN DASAR DI SDIT ‘HARAPAN UMAT” KABUPATEN JEMBER - Iswahyono Iswahyono; Siti Djamila; R. Abdoel Djamali; Amal Bahariawan (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Along with the dynamics of population growth and economic growth targets, especially in urban areas, the availability of land for agricultural cultivation is increasingly difficult and increasingly narrow. This means that the agricultural sector is increasingly marginalized due to pressure and the development of other sectors that have led to the massive conversion of agricultural land functions. The purpose of this community service activity is to produce educators (trainers) at the basic education level about the introduction of hydroponic cultivation. The implementation methodology: (1) as the target audience, namely SDIT Harapan Jember teachers, (2) the approach methods used are: (a) classically in delivering the material and (b) field practice, namely participants directly carrying out hydroponic cultivation practices starting from determining the equipment. and materials, seedlings, planting, to proper and correct harvesting methods, (3) Tools and materials used: hydroponic cultivation manuals, production facilities, and hydroponic cultivation installations. The results of the activity show that: (a) the number of participants is 10 teachers, (b) material presented: prospects and opportunities for hydroponic cultivation, hydroponic cultivation techniques, and harvesting and postharvest, (c) the results of the evaluation of the implementation of the activity show an average score of 4.32, namely the Good category, (d) the level of mastery of theory and practice, the average score of the actual post-test score is 6.7 (good enough category).